Refined polysaccharide from Dendrobium devonianum resists H1N1 influenza viral infection in mice by activating immunity through the TLR4/MyD88/NF-κB pathway - Wei, Xueping; Sun, Wei; Zhu, Pengpeng; Ou, Guoteng; Zhang, Sheng; Li, Yuanyuan; Hu, Jingjin; Qu, Xuefeng; Zhong, Yan; Yu, Wenying; You, Zhenqiang; Wang, Yin; et al. (Frontiers in Immunology, 2022)
Dendrobium polysaccharide exhibits multiple biological activities, such as immune regulation, antioxidation, and antitumor activities. However, its resistance of viral infection by stimulating immunity is rarely reported. In this study, we explored the effect and mechanism of DVP-1, a novel polysaccharide from Dendrobium devonianum, in the activation of immunity. After being activated by DVP-1, the ability of mice to prevent H1N1 influenza virus infection was investigated. The results of immune regulation showed that DVP-1 significantly improved the immune organ index, lymphocyte proliferation, and mRNA expression level of cytokines, such as IL-1β, IL-4, IL-6, and TNF-α, in the spleen. Immunohistochemical results showed that DVP-1 obviously promoted the mucosal immunity in the jejunum tissue. In addition, the expression levels of TLR4, MyD88, and TRAF6, and the phosphorylation levels of TAK1, ERK, JNK, and NF-κB in the spleen could be up-regulated by DVP-1. The virus infection results showed that the weight loss of mice slowed down, the survival rate increased, the organ index of lung reduced, and the virus content in lung decreased after DVP-1 activated immunity. By activating immunity with DVP-1, the production of inflammatory cells and inflammatory factors in BALF, and alveolar as well as peribronchiolar inflammation could be prevented. The results manifested that DVP-1 could resist H1N1 influenza virus infection by activating immunity through TLR4/ MyD88/ NF-κB pathway.